PERSEPSI ANGGOTA ATAS PELAYANAN KREDIT PADA CU KHATULISTIWA BAKTI PONTIANAK - Ramadhani, Lutfia Nur; Khosmas, Khosmas; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze member perceptions of Service Accuracy, analyze member perceptions on friendly Service, analyze member's perceptions of comfort in getting service and To know what efforts are done by CU Khatulistiwa Bakti Pontianak in improving Member Service. The focus of the research is the member's perception of credit service at CU Khatulistiwa Bakti Pontianak, sub focus: 1. Service Accuracy 2. Friendly service 3. comfort in getting service.  The research method is descriptive method with  survey form. The study population was 51,637 members and the study sample was 100 members. Research using direct communication techniques, indirect communication and documentary study techniques. Data collection tools for interview guides, questionnaires and notebooks. Research was analyzed based on quantitative descriptive. Results The membersperceptions of the accuracy of service, the hospitality of the service, the comfort in obtaining the services provided by the employee are well viewed from the answers of the members at most well. The results showed that the perception of members of credit services at CU Khatulistiwa Bakti Pontianak has 77.3% percentage is in the high category. It is concluded that the credit service provided by Credit Union Khatulistiwa Bakti Pontianak is good.        Keywords: Perception, Member, Credit Service